(untitled) (Faridpur Medical College Journal, 2017)
The objectives of this present study is to evaluate the clinical profile and pattern of various drugs used in the treatment of typhoid fever. A retrospective analysis of Paediatric patients suffering from typhoid fever was done at Department of Paediatrics, Faridpur Medical College Hospital, Faridpur during the year 2015-2016. Diagnosis of patients was based on clinical features, Widal test and blood culture. The sensitivity pattern of isolates from blood culture was recorded. The mode of presentation, clinical course, treatment history, laboratory investigations reports, antibiotic administered, response to therapy and the complications were recorded. Total number of 50 cases of typhoid fever were studied. Out of these 23 (46%) were males and 27 (54%) were females. Average age of presentation was 8.2 years. Average duration of hospital stay was 10.8 days. Fever was present in all patients. Resistance of S. typhi to amoxicillin, chloramphenicol, ampicillin and co-trimoxazole were significantly high. Ciprofloxacin also showed resistance in 21.4% of cases. Sensitivity to cephalosporin was 100% in our study. Ciprofloxacin was the most commonly used antibiotic in our study (26 patients). Chloramphenicol alone was used in 2 patients and in 3 patients it was given after 6 days of ciprofloxacin treatment. Third generation cephalosporin (ceftriaxone) alone were used in 10 patients. Indiscriminate use of drugs in typhoid fever should be discouraged. Appropriate antibiotic as indicated by sensitivity tests should be employed to prevent the development of resistant strains of S. typhi. Faridpur Med. Coll. J. Jan 2017;12(1): 2-4